Indole-derived chalcones as anti-dermatophyte agents: In vitro evaluation and in silico study. (February 2020) - Mirzaei, Hassan; Abastabar, Mahdi; Emami, Saeed
Graphical abstract: Highlights: Indole-derived methoxylated chalcones were introduced as anti-dermatophyte agents. Most of compounds had potent activity against dermatophyte strains. Compound 4d was the most potent compound against T. interdigitale, T. veruccosum and M. fulvum (MICs = 0.25−2 μg/ml). 3D-structure of the target protein (tubulin) was modeled by homology modeling and used for docking and MD simulations. Abstract: A series of indole-derived methoxylated chalcones were described as anti-dermatophyte agents. The in vitro antifungal susceptibility testing against different dermatophytes revealed that most of compounds had potent activity against the dermatophyte strains. In particular, the 4-ethoxy derivative 4d with MIC values of 0.25−2 μg/ml was the most potent compound against Trichophyton interdigitale, Trichophyton veruccosum and Microsporum fulvum . Moreover, the 4-butoxy analog 4i displaying MIC values in the range of 1−16 μg/ml had the highest inhibitory activity against Trichophyton mentagrophytes, Microsporum canis, and Arthroderma benhamiae . To predict whether the synthesized compounds interact with tubulin binding site of dermatophytes, the 3D-structure of target protein was modeled by homology modeling and then used for molecular docking and molecular dynamics (MD) simulation studies. Docking simulation revealed that the promising compound 4d can properly bind with tubulin. The molecular dynamics analysis showed that interactions of compound 4d with the active site of target protein have binding stability throughout MD simulation. The results of this study could utilize in the design of more effective antifungal drugs with tubulin inhibition mechanism against keratinophilic fungi.